A Review: Metal Filled Thermoset Composites. Issue 1 (2nd January 2022) - Zaaba, Nor Fasihah; Ismail, Hanafi; Saeed, Alaa Muhsin
ABSTRACT: Metal filled composites are rapidly gaining their place in various distinct industrial and domestic applications. They made of polymer binders (thermosets) such as epoxy, silicone and polyurethane incorporated with metallic or conductive fillers, such as silver, copper, nickel, gold, etc., offered mechanical strength with improved thermal conductivity. Due to their unique properties, such as high specific strength and stiffness with relatively low weight, high corrosion resistance and controllable conductivity, metal filled thermoset composites have been used in various industries including electrical and electronic, medical, aircraft and automotive industry. Unfortunately, filler–matrix adhesion, filler dispersion and high material and manufacturing costs caused the implementation of these materials more challenging. Additives such as coupling agents were introduced to improve the performances of metal filled thermoset composites. This review paper covers the fundamentals of thermoset polymer properties, processing method of metal powder, the preparation and characterization of metal filled thermoset composites from previous studies and the advantages and disadvantages of these materials in various industries. Graphical abstract: uf0001